Isolation and Characterization of Prototrophic Mutants of Escherichia coli Unable to Support the Intracellular Growth of T7 - Chamberlin, Michael (1974)
Mutants of E. coli B/1 were isolated which grew normally but did not permit the intracellular growth of bacteriophage T7. Two classes of mutants were studied in detail (tsnB(−) and tsnC(−)). These strains adsorbed T7 normally and were killed by the infection. Synthesis of T7 RNA and of early and late classes of T7 proteins occurred normally after infection. In T7-infected tsnB(−) cells, T7 DNA synthesis stopped prematurely shortly after its onset, suggesting that the tsnB function affects a step in the late phase of T7 DNA replication. Mutants of T7 were isolated (T7β) which could grow on tsnB(−) cells. In T7-infected tsnC(−) cells, T7 DNA synthesis was completely blocked, suggesting that the tsnC function affects a step in an early phase of T7 DNA replication.